2004
DOI: 10.1097/00008571-200412000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase gene polymorphisms and response to fluorouracil-based treatment in advanced colorectal cancer patients

Abstract: Methylenetetrahydrofolate reductase (MTHFR) controls intracellular CH2FH4 concentrations (required for optimal fluoropyrimidine efficacy) by irreversibly converting CH2FH4 into 5-methyltetrahydrofolate. MTHFR 677C>T and 1298A>C polymorphisms are linked to altered enzyme activity. Thus, mutated MTHFR tumours should, in theory, be more sensitive to 5-fluorouracil (5FU) than wild-type tumours. MTHFR polymorphisms in position 677 and 1298 were analysed in 98 colorectal cancer patients with unresectable liver metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 27 publications
7
80
2
3
Order By: Relevance
“…Etienne et al also showed that SNPs at MTHFR-A1298C were unrelated to the outcome of 5-FU-based chemotherapy in the clinical setting, but were significantly linked to survival, with homozygous mutated (CC) patients having the worst prognosis (12). This also supported previous findings (23).…”
Section: ------------------------------------------------------------supporting
confidence: 59%
See 1 more Smart Citation
“…Etienne et al also showed that SNPs at MTHFR-A1298C were unrelated to the outcome of 5-FU-based chemotherapy in the clinical setting, but were significantly linked to survival, with homozygous mutated (CC) patients having the worst prognosis (12). This also supported previous findings (23).…”
Section: ------------------------------------------------------------supporting
confidence: 59%
“…Predicting the direction of the metabolic pathway of reductive folates, whether for DNA synthesis or methylation, is crucial for determining the susceptibility of cancers to antimetabolites such as 5-FU. Two single nucleotide polymorphisms (SNPs) of MTHFR, C677T and A1298C, alter the activity of the methylenetetrahydrofolate reductase enzyme, and have been intensively evaluated for their association with 5-FU efficacy (11)(12)(13). However, there are many discrepancies between the results.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that the MTHFR 677T mutation, linked to the reduced activity of MTHFR, increases chemosensitivity to 5-FU (Cohen et al, 2003;Sohn et al, 2004), whereas others have had inconsistent results (Etienne et al, 2004;Ruzzo et al, 2006). Although MTHFR and DHFR are key enzymes in folate metabolism, the role of MTHFR gene expression in the antitumour activity of 5-FU remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…46 In a recent study of 98 dissiminated colorectal cancer patients, the C677T mutation was also associated with higher response rates on 5-FU/folinic acid chemotherapy. 47 In the same study, the A1298C polymorphism was studied, but this was not related to the response rate. The exact roles of the MTHFR polymorphisms have to be elucidated in larger prospective clinical trials.…”
Section: -Fluorouracilmentioning
confidence: 99%